Kiwifruit Allergy—Molecular Basis, Diagnostics and Treatment - Elaine M. Wright; Andrea O’Malley; Kriti Khatri; Rebekka Pittsley; Lesa R. Offermann; Emily Covert; Tiffany Ruan; Maria Antonietta Ciardiello; Krzysztof Kowal; Maksymilian Chruszcz (Applied Sciences)
Kiwifruit allergy was first described over 40 years ago and is becoming increasingly common worldwide. This is most likely related to the fact that kiwifruit production and consumption increased by almost two orders of magnitude during the last 50 years. Currently, there are thirteen officially registered allergens belonging to the species Actinidia deliciosa (green kiwifruit), and three officially registered allergens belonging to the species Actinidia chinensis (golden kiwifruit). The molecular properties of the kiwifruit allergens are summarized, and their features are discussed, considering the protein families to which they belong. At present, kiwifruit allergens are found to belong to 13 protein families. Allergic reactions caused by these molecules can be local, for example, related to the oral cavity, but in some cases systemic responses, such as anaphylaxis, are also observed. Generally, kiwifruit allergy should not be considered as a homogenous disorder, as it was noted that there are distinct groups of patients with different sensitization profiles. Therefore, the diagnostic process may be challenging, as in many cases other food allergies must be considered. Frequently cross-reactivity between kiwifruit allergens and their homologs originating from other organisms has a significant impact on the wellbeing of the affected individuals.